Differential immunoregulation by human surfactant protein A variants determines severity of SARS-CoV-2-induced lung disease - Jacob, Ikechukwu B.; Lawal, Akinkunmi O.; Mahmoud, Salma S.; Kopsack, Emerson M.; Reynolds, Erin S.; Meng, Qinghe; Fan, Hongkuan; Massa, Paul T.; Thangamani, Saravanan; Jia, Hongpeng; Wang, Guirong (Frontiers in Immunology, 2025)
IntroductionCOVID-19 remains a significant threat to public health globally. Infection in some susceptible individuals causes life-threatening acute lung injury (ALI/ARDS) and/or death. Human surfactant protein A (SP-A) is a C-type lectin expressed in the lung and other mucosal tissues, and it plays a critical role in host defense against various pathogens. The human SP-A genes (SFTPA1 and SFTPA2) are highly polymorphic and comprise several common genetic variants, i.e., SP-A1 (variants 6A2, 6A4) and SP-A2 (variants 1A0, 1A3). Here, we elucidated the differential antiviral and immunoregulatory roles of SP-A variants in response to SARS-CoV-2 infection in vivo.MethodsSix genetically-modified mouse lines, expressing both hACE2 (SARS-CoV-2 receptor) and individual SP-A variants: (hACE2/6A2 (6A2), hACE2/6A4 (6A4), hACE2/1A0 (1A0), and hACE2/1A3 (1A3), one SP-A knockout (hACE2/SP-A KO (KO) and one hACE2/mouse SP-A (K18) mice, were challenged intranasally with 103 PFU SARS-CoV-2 or MEM medium (Sham).ResultsInfected KO and 1A0 mice had more weight loss and mortality compared to other mouse lines. Relative to other infected mouse lines, a more severe ALI was observed in KO, 1A0, and 6A2 mice. Reduced viral titers were generally observed in the lungs of infected SP-A mice relative to KO mice. Transcriptomic analysis revealed an upregulation in genes that play central roles in immune responses such as MyD88, Stat3, IL-18, and Jak2 in the lungs of KO and 1A0 mice. However, Mapk1 was significantly downregulated in 6A2 versus 1A0 mice. Analysis of biological pathways identified those involved in lung host defense and innate immunity, including pathogen-induced cytokine, NOD1/2, and Trem1 signaling pathways. Consistent with the transcriptomic data, levels of cytokines and chemokines such as G-CSF, IL-6, and IL-1β were comparatively higher in the lungs and sera of KO and 1A0 mice with the highest mortality rate. Furthermore, we observed the complexity of COVID-19, such as the difference between lung and systemic immune response to viral infection and of viral load and mortality among SP-A variants in this model.ConclusionThese findings demonstrate that human SP-A variants differentially modulate SARS-CoV-2-induced lung injury and disease severity by differentially inhibiting viral infectivity and regulating immune-related gene expressions.